Concussion vs. resignation by submission: Technical–tactical behavior analysis considering injury in mixed martial arts - Miarka, Bianca; Soto, Dany A. Sobarzo; Aedo-Muñoz, Esteban A.; Maurício, Clóvis A.; Müller, Vanessa T.; Bragazzi, Nicola L.; Brito, Ciro José (Frontiers in Neurology, 2022)
This research study verified the technical–tactical actions during the mixed martial arts (MMA) fights to generate serious enough injury to stop the MMA round, determining technical-tactical potential risk factors for injury in official MMA combats, according to Concussion or Resignation per Submission. A total of 990 rounds with concussions and 627 resignations per submission were considered with severe injury (i.e., a fight ended by a doctor or referee). All injuries were diagnosed and managed by attending ringside physicians during the MMA fights and rounds and had a continuous technical–tactical behavior analysis, p ≤ 0.05. The leading cause of concussion was due to head trauma (~90%), with higher dependence on head strikes scored actions. Comparisons between Concussion and Resignation per Submission combats demonstrated differences between distance head strikes actions [13(6,25) vs. 9(4,18) frequencies], clinch head strikes actions [1(0;4) vs. 1(0;3) frequencies], ground head strikes actions [1(0;8) vs. 2(0;10) frequencies] and takedowns actions [0(0;1) vs. 1(0;2) frequencies]. This information may provide significant evidence regarding the doctor stoppage in concussion combats and when it could be called by officials supervising MMA.